PELANGGARAN HAK KEKEBALAN DIPLOMATIK ATAS DUTA BESAR ITALIA YANG DITAHAN DI INDIA DITINJAU DARI HUKUM INTERNASIONAL - Natasa Fransiska Elisabeth Siahaan; Sutiarnoto Sutiarnoto; Arif Arif (Journal of USU International Law, 2014)
ABSTRACT There is nosingle country inthe worldthatcanliberatethemselvesfrominvolvement withother countries. Becauseof the importanceof a countryinanotherregion ofthecountry, then relationshipwas created. Therefore, diplomaticrepresentative is determinedtoestablishfriendly relationsand to enhancecooperation betweenthe twocountries. However, there are still manycases thatthreatenoffendersdiplomatsanddiplomaticimmunityand privileges. It is as in thecase ofdetentionItalian AmbassadorinIndia. Then, it  poses the question;how is the diplomaticrecognition ofrightsin international law? Howis the infringementsettlementimmunityand privileges ofdiplomaticrepresentationin termsofinternational law? Howis the infringement casesof immunityandprivilege inanItalianambassadorinIndia? The research methodusedwas library research approach ornormativeresearch, namely theeffortof selectingandcollecting datafroma wide variety ofbooks, scholarsopinion, dictionary, encyclopedia, and literatureof internationallawandinternationalpoliticalrelationsrelating tothesis writing.